Ten things to know about oomycete effectors - Schornack, Sebastian (2009)
Long considered intractable organisms by fungal genetic research standards, the oomycetes have recently moved to the centre stage of research on plant-microbe interactions. Recent work on oomycete effector evolution, trafficking and function has led to major conceptual advances in the science of plant pathology. In this review, we provide a historical perspective on oomycete genetic research and summarize the state of the art in effector biology of plant pathogenic oomycetes by describing what we consider to be the 10 most important concepts about oomycete effectors.